A single administration of Neurotropin reduced the elongated immobility time in the forced swimming test of rats exposed to repeated cold stress. Issue 7 (October 2019) - Nasu, Teruaki; Kubo, Asako; Queme, Luis F.; Mizumura, Kazue
Abstract : Many people suffer from a major depressive disorder, and chronic pain conditions are often associated with depressive symptoms. Neurotropin, an extract from the inflamed skin of rabbits inoculated with vaccinia virus, has been used for pain relief. Decrease of brain-derived neurotrophic factor (BDNF) in the brain is one of the proposed mechanisms for the major depressive disorders, and Neurotropin has been reported to restore the decreased BDNF in the hippocampus. In this experiment, we examined whether Neurotropin had an antidepressant-like effect in a model of fibromyalgia and whether BDNF in the brain was altered after repeated cold stress (RCS) and Neurotropin treatment. Rats were exposed to RCS because these animals have been used as a model for fibromyalgia syndrome. Depression-like behavior was evaluated using elongation of immobility time in a forced swimming test. Change in expression of BDNF in the brain was also examined by western blot analysis of several brain areas. Depression-like behavior in the forced swimming test was significantly increased 10–14 days after RCS, and this increase was reversed by a single injection of an antidepressant, imipramine, but not by PBS. Increased depression-like behavior was also dose-dependently suppressed by a single administration of Neurotropin (50–200 NU/kg, subcutaneously). BDNF expression was not changed in the brain areas examined (hippocampus, amygdala, prefrontal cortex, and striatum) either after RCS or by Neurotropin injected after RCS. These results suggest that RCS induced a depression-like state in rats, and Neurotropin reversed this state. However, we did not observe a BDNF-related mechanism for these effects.